2013
DOI: 10.1523/jneurosci.5858-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Protein Hermes/RBPMS Inversely Affects Synapse Density and Axon Arbor Formation in Retinal Ganglion Cells In Vivo

Abstract: The RNA-binding protein Hermes [RNA-binding protein with multiple splicing (RBPMS)] is expressed exclusively in retinal ganglion cells (RGCs) in the CNS, but its function in these cells is not known. Here we show that Hermes protein translocates in granules from RGC bodies down the growing axons. Hermes loss of function in both Xenopus laevis and zebrafish embryos leads to a significant reduction in retinal axon arbor complexity in the optic tectum, and expression of a dominant acting mutant Hermes protein, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
79
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 56 publications
(83 reference statements)
5
79
0
Order By: Relevance
“…For example, zip-code binding protein 1 (ZBP1, also called IGF-II mRNA binding [IMP1]) protein was shown to bind to a 56 nucleotide (nt) stem-loop structure in the 3' untranslated region (UTR) of β-actin mRNA (Actb), and this binding is necessary for axonal transport of the mRNA (6,7). Other RBPs implicated in axonal mRNA transport include nucleolin (Ncl), HuD (also called ELAVL4), hnRNP Q, hnRNP R, splicing factor proline and glutamine-rich (SFPQ), fragile X mental retardation (FMRP), Hermes, TRF2-S, and TDP-43 proteins (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Despite increased insight into RNA transport and translation, including the identification of literally thousands of axonal mRNAs (18,19), relatively few RBPs have been identified in axons.…”
Section: Introductionmentioning
confidence: 99%
“…For example, zip-code binding protein 1 (ZBP1, also called IGF-II mRNA binding [IMP1]) protein was shown to bind to a 56 nucleotide (nt) stem-loop structure in the 3' untranslated region (UTR) of β-actin mRNA (Actb), and this binding is necessary for axonal transport of the mRNA (6,7). Other RBPs implicated in axonal mRNA transport include nucleolin (Ncl), HuD (also called ELAVL4), hnRNP Q, hnRNP R, splicing factor proline and glutamine-rich (SFPQ), fragile X mental retardation (FMRP), Hermes, TRF2-S, and TDP-43 proteins (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Despite increased insight into RNA transport and translation, including the identification of literally thousands of axonal mRNAs (18,19), relatively few RBPs have been identified in axons.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of RBPMS family proteins has been reported in cancer (Skawran et al 2008;Miller and Stamatoyannopoulos 2010;Drozdov et al 2012;Hapkova et al 2013; http://www.cbioportal.org/public-portal/) and chronic intestinal pseudo-obstruction (Notarnicola et al 2012). Manipulation of RBPMS levels during embryogenesis suggested functions in X. laevis oocyte maturation (Zearfoss et al 2003), heart and kidney development (Gerber et al 2002), and retinal ganglion cell development (Hornberg et al 2013). In X. laevis RBPMS regulated cleavage of vegetal blastomeres in early embryogenesis (Zearfoss et al 2004) and was suggested to control mRNA processing (Gerber et al 2002;Song et al 2007) and transport of mRNAs along the axon to the axon terminal of retinal ganglion cells (Hornberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Manipulation of RBPMS levels during embryogenesis suggested functions in X. laevis oocyte maturation (Zearfoss et al 2003), heart and kidney development (Gerber et al 2002), and retinal ganglion cell development (Hornberg et al 2013). In X. laevis RBPMS regulated cleavage of vegetal blastomeres in early embryogenesis (Zearfoss et al 2004) and was suggested to control mRNA processing (Gerber et al 2002;Song et al 2007) and transport of mRNAs along the axon to the axon terminal of retinal ganglion cells (Hornberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A fascinating, in our opinion, characteristic of the Rbpms expression profile is that although this gene is expressed in various tissues, in the adult CNS, it was restricted to RGCs. In a recent study to investigate the role of Rbpms in the retina, it has been shown that Rbpms loss of function in both Xenopus laevis and zebrafish embryos results in a significant reduction in retinal axon arbor complexity in the optic tectum (Hörnberg et al 2013). At the same time, an increase in the density of presynaptic puncta was observed in these animals, suggesting that reduced arborization is accompanied by increased synaptogenesis to maintain synapse number.…”
Section: Introductionmentioning
confidence: 99%